DiPODS: A Reagent for Site-Specific Bioconjugation via the Irreversible Rebridging of Disulfide Linkages - Sarbisheh, Elaheh Khozeimeh (Bioconjug Chem, 2020)
Chemoselective reactions with thiols have long held promise for the site-specific bioconjugation of antibodies and antibody fragments. Yet bifunctional probes bearing monovalent maleimides — long the ‘gold standard’ for thiol-based ligations — are hampered by two intrinsic issues: the in vivo instability of the maleimide-thiol bond and the need to permanently disrupt disulfide linkages in order to facilitate bioconjugation. Herein, we present the synthesis, characterization, and validation of DiPODS, a novel bioconjugation reagent containing a pair of oxadiazolyl methyl sulfone moieties capable of irreversibly forming covalent bonds with two thiolate groups while simultaneously re-bridging disulfide linkages. The reagent was synthesized from commercially available starting materials in 8 steps, during which rotamers were encountered and investigated both experimentally and computationally. DiPODS is designed to be modular and can thus be conjugated to any payload through a pendant terminal primary amine (DiPODS–PEG(4)-NH(2)). Subsequently, the modification of a HER2-targeting Fab with a fluorescein-conjugated variant of DiPODS (DiPODS-PEG(4)-FITC) reinforced the site-specificity of the reagent, illustrated its ability to rebridge disulfide linkages, and produced an immunoconjugate with in vitro properties superior to those of an analogous construct created using traditional stochastic bioconjugation techniques. Ultimately, we believe that this work has particularly important implications for the synthesis of immunoconjugates, specifically for ensuring that the attachment of cargoes to immunoglobulins is robust, irreversible, and biologically and structurally benign.